Efficacy of individualized homeopathic treatment of insomnia: Double-blind, randomized, placebo-controlled clinical trial. (April 2019) - Michael, James; Singh, Subhas; Sadhukhan, Satarupa; Nath, Arunava; Kundu, Nivedita; Magotra, Nitin; Dutta, Susmit; Parewa, Maneet; Koley, Munmun; Saha, Subhranil
Highlights: We evaluated whether individualized homeopathy (IH) could produce significant effect beyond placebo in treatment of insomnia. In this double-blind, randomized, placebo-controlled, two parallel arms trial, 60 patients were randomized in 1:1 ratio to receive either IH or placebo. Patient-administered sleep diary (6 items) and Insomnia Severity Index (ISI) were taken as the primary and secondary outcomes respectively, measured at baseline, and after 3 months. Group differences were significant for sleep diary items 4, 5 and 6 ( P < 0.01) and just significant ( P = 0.014) for ISI score with moderate to large effect sizes; but non-significant for rest of the outcomes. IH seemed to produce significantly better effect than placebo in treatment of insomnia. Abstract: Background: Insomnia is the most common sleep-related complaint associated with impaired day-time functioning, reduced quality of life, increased morbidity and substantial societal cost. We evaluated whether individualized homeopathy (IH) could produce significant effect beyond placebo in treatment of insomnia. Methods: In this double-blind, randomized, placebo-controlled, two parallel arms trial, 60 patients were randomized to receive either IH/verum or control/placebo (1:1). Patient-administered sleep diary (6 items; 1: latency to fall asleep, 2: minutes awake in middle of night, 3: minutes awake too early, 4: hours spent in bed, 5: total sleep time in hours, and 6: sleep efficiency) and Insomnia Severity Index (ISI) were taken as the primary and secondary outcomes respectively, measured at baseline, and after 3 months. Results: Five patients dropped out (verum: 2, control: 3). Intention to treat sample (n = 60) was analyzed. Trial arms were comparable at baseline. In the verum group, except sleep diary item 3 ( P = 0.371), rest of the outcomes improved significantly (all P < 0.01). In the control group, there were significant improvements in diary item 6 and ISI score ( P < 0.01) and just significant improvement in item 5 ( P = 0.018). Group differences were significant for items 4, 5 and 6 ( P < 0.01) and just significant ( P = 0.014) for ISI score with moderate to large effect sizes; but non-significant ( P > 0.01) for rest of the outcomes. Conclusion: IH seemed to produce significantly better effect than placebo. Rigorous trials and independent replications are warranted.